Family and social change in an African city - Marris, Peter (London, 1961)
This book some of these changes in the capital city of the largest of the new African states. It is based on an enquiry into the family relationships and means of livelihood of the people of central Lagos, and the way in which slum clearance affected them. I decided to relate the study of change to an examination of the Lagos slum clearance scheme, partly because a previous study by the Institutel had discussed the effects of slum clearance on family life in London, and some of its con clusions might be relevant in the context of African city planning; but more especially because although the Lagos scheme only bears on a minority of the city's population, it illustrates very concretely the implications of social change. The design of a house, the layout of a street, mould social behaviour, and influ ence very directly the way in which people live. They interpret in terms of physical space the ideals by which planners believe social relationships should be formed. Housing policy is therefore much influenced by the most articulate values of society. On a new housing estate, private life is framed within the provisions of public policy. At the same time , latent changes in social structure become manifest in reaction to new surroundings.
Keywords: Sociology